Causes of Enhanced Bromine Levels in Alpine Ice Cores During the 20th Century: Implications for Bromine in the Free European Troposphere. Issue 8 (26th April 2021) - Legrand, M.; McConnell, J. R.; Preunkert, S.; Chellman, N. J.; Arienzo, M. M.
Abstract: Total bromine (Br) was investigated in seasonally resolved alpine ice cores covering the 20th century. Results revealed increased Br concentrations in summer (from 0.7 ng g −1 in the late 1940s to 1.6 ng g −1 in the mid 1970s), followed by a slight decrease to 1.25 ng g −1 during the last decade of the 20th century. In winter, a more moderate increase was observed from before 1950 (0.35 ng g −1 ) to the 1970–2000 period (∼0.50 ng g −1 ). Measurements of lead suggest that ∼75% of the bromine increase in summer alpine ice between 1930–1950 and 1965–1985 was from bromine‐containing aerosol (PbBrCl) emitted during the combustion of leaded gasoline. This contribution decreased to ∼27% in 2000 following the large decrease of lead additive content in gasoline used in western Europe. Summer ice bromine concentrations, not related to PbBrCl aerosol (denoted Bry *), increased by 40% from the late 1940s to the 1990–2000 decade. In winter, the contribution of leaded‐gasoline aerosol to total bromine levels was weaker than in summer, with the winter bromine trend mainly caused by enhanced Bry * levels (∼40%) after 1950. These Bry * variations in glacial ice are discussed in terms of past atmospheric reactive bromine (Bry ) changes in the European troposphere, including anthropogenic CH3 Br emissions and transport from the stratosphere. Plain Language Summary: Bromine chemistry plays an important role in tropospheric chemistry, influencing the levels of ozone and several other key atmospheric species, including HOx and NOx radicals. Measurements conducted in alpine ice cores spanning the 20th century showed a doubling of total bromine from the late 1940s to the 1980–1990s. This first identification of changes in bromine in ice cores extracted outside polar regions, where ice records are strongly influenced by the sea‐ice process, is of interest for bromine chemistry model simulations of past, present, and future tropospheric ozone changes in the midlatitudes. It is shown that alpine ice core records contain information on past bromine particles emitted by leaded‐gasoline combustion, revealing the rapid growth of these anthropogenic emissions from 1950 to 1975 and the subsequent decline caused by the reduced use of lead additive in gasoline in western Europe. In addition to changes in the aerosol component, the remaining part of the observed increase of total bromine in alpine ice is attributed to enhanced levels of inorganic bromine gaseous species resulting from anthropogenic emissions, including CH3 Br (fumigation). Key Points: Alpine ice revealed a twofold increase in total bromine, mainly after 1950 Bromine trends in alpine ice attributed to aerosol from leaded‐gasoline use and reactive gases from anthropogenic CH3 Br emissions